Effect of Using Moringa Leave (Moringa Oleifera L.) and Pineapple (Ananas Comosus) Leaf Lotion Gel Lotion on Skin Moisture - Ariyanti Ariyanti; Eni Masruriati; Dwi Setyowati; Filza Mazaya Nurulita (Global Health Science Group, 2023)
The compounds contained in Moringa leaves are rich in phenolic acids, flavonoids, alkaloids, tannins, glucosinolates and isothiocyanates, all of which are antioxidants. Moringa leaves contain B2 which is useful for treating and maintaining skin moisture. Pineapple fruit contains vitamin C and vitamin A, the second vitamin is known to have antioxidant activity that can stop the reaction of forming free radicals. Moringa leaves and pineapple contain antioxidant compounds which are useful as skin moisturizers which are formulated in the form of a gel lotion. This study aims to determine the effect of using moringa leaf extract gel lotion and pineapple fruit on skin moisture. This study was initiated by formulating lotion preparations with the addition of concentrations of moringa leaf extract and pineapple fruit, namely concentrations of 3% (F1) 4% (F2) 5% (F3). Lotion gel was evaluated for physical stability by testing pH, viscosity, adhesion, spreadability, irritation test, specific gravity test and skin moisture test. This study uses an experimental method. The results showed that the formula concentrations of 3%, 4% and 5% all met the requirements of the physical stability test as a skin moisturizing lotion gel preparation. The higher the concentration of the extract, the wider the spreadability and viscosity value obtained, has no effect on adhesion and pH value. Lotion preparations of moringa leaf and pineapple fruit extracts with a concentration of 5% have a high ability as skin moisturizers. The results showed that the formula concentrations of 3%, 4% and 5% all met the requirements of the physical stability test as a skin moisturizing lotion gel preparation. The higher the concentration of the extract, the wider the spreadability and viscosity value obtained, has no effect on adhesion and pH value. Lotion preparations of moringa leaf and pineapple fruit extracts with a concentration of 5% have a high ability as skin moisturizers. The results showed that the formula concentrations of 3%, 4% and 5% all met the requirements of the physical stability test as a skin moisturizing lotion gel preparation. The higher the concentration of the extract, the wider the spreadability and viscosity value obtained, has no effect on adhesion and pH value. Lotion preparations of moringa leaf and pineapple fruit extracts with a concentration of 5% have a high ability as skin moisturizers.